(untitled) (Bangladesh Journal of Medical Science, 2016)
Background: Acute encephalitis syndrome (AES) is one of cortical visual impairment (CVI) causes. There were only few studies about cortical visual involvement in children with AES. Objective: To describe CVI in children with AES. Methods: This study included all children with AES during January to March 2014, were examined for visual evoked potential (VEP) to evaluate cortical visual pathway. AES was defined as clinical condition characterized by acute onset of fever, a change in mental status, and/or new onset of seizures. CVI was defined as vision loss caused by central nervous system damage confirmed by VEP. Results: There were 9 children with AES and all showed bilateral CVI. The age range between 6 to 48 months old, with 7 males and 2 females. Visual evoked potential result showed 8 children with demyelinating type and 1 with axonal type. Conclusion: Type of CVI caused by AES can be demyelinating type or axonal type. Bangladesh Journal of Medical Science Vol.15(2) 2016 p.249-251